Cooperative Work Support and Automatic Design Verification in Architecture and Building Construction - Dias, J.; Galli, R.; Gamito, M. N. (Proc eSM@RT 2002 - Towards a European Knowledge Economy in the Construction & Related Sectors, The European Conference on Information and Communication Technology Advances and Innovation in the Knowledge Society, University of Salford, UK, 2002)
XXX